Biotechnological potentialities and valorization of mango peel waste: a review - Puligundla, Pradeep; Sarathi Reddy Obulam, Vijaya; Sang Eun Oh; Chulkyoon Mok (Universiti Kebangsaan Malaysia, 2014)
In recent years, by-products of fruit processing have received a great deal of attention, which is primarily due to their nutritional and economic exploitation through utilization of emerging technologies. Mango peel waste, a by-product from pulp processing units, is an important source of high quality antioxidant dietary fibre, pectin, polyphenols and carotenoids. It also possess significant biotechnological potential since it has been found suitable for several bioprocesses including ethanol, biogas, lactic acid, enzymes and single cell production. Valorization of mango peel through different routes not only can increase the profitability of fruit processing industries, but also help reduce environmental pollution. This review intends to provide a broad view on available technologies for mango peel waste utilization, with an emphasis on its biotechnological conversion into added value products beside other ways of utilization.